THE INFLUENCE OF PROFITABILITY, LIQUIDITY AND LEVERAGE ON STOCK RETURN WITH DIVIDEND POLICY AS A MODERATION VARIABLE IN COMPANIES LISTED IN THE INDONESIA STOCK EXCHANGE LQ45 INDEX - Julianti, Merline; Khaddafi, Muammar; Robin, Robin; Satriawan, Bambang (CV. Radja Publika, 2022)
This study aims to determine the effect of profitability, liquidity and leverage on stock returns and determine the ability of dividend policy in moderating the relationship between profitability, liquidity and leverage on stock returns in companies listed on the LQ45 index of the Indonesia Stock Exchange. The sample used in this study are companies listed on the LQ45 index of the Indonesia Stock Exchange which have retained earnings, pay dividends for three consecutive years and use Rupiah currency. The data analysis method used in this research is multiple linear regression analysis method. This study was conducted with a total of 20 samples of companies listed on the LQ45 index of the Indonesia Stock Exchange from the period 2019 to 2021. The results of data testing partially found that profitability and liquidity had a significant positive effect on stock returns, while leverage had a negative and insignificant effect on stock returns. . The results of testing the moderating data conclude that dividend policy is not able to moderate the relationship between profitability and liquidity to stock returns, while dividend policy is able to moderate the relationship between leverage and stock returns.